The Effect of Soft Skills, Hard Skills, and Compliance on Employee Performance Through Self-Awareness as an Intervening Variable at the Regional Personnel and Human Resource Development Agency (BKPSDM) of Medan City - Bayu Permana Wibowo; Prihatin Lumbanraja; R. Hamdani Harahap (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Employee performance is a key element in realizing organizational goals and optimizing public services. The Regional Personnel and Human Resource Development Agency (BKPSDM) of Medan City, as a government agency responsible for managing civil servants (ASN), needs to continuously improve employee performance, particularly in the face of bureaucratic reform challenges. This study aims to analyze the effect of soft skills, hard skills, and compliance on employee performance at BKPSDM Medan City, with employee self-awareness as an intervening variable. This research is associative in nature with a quantitative approach. Primary data were collected through questionnaires. The analytical method applied was descriptive statistical analysis and Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The research population comprised all ASN employees working in 5 divisions at BKPSDM Medan City, totaling 72 employees, with a census (total sampling) technique. Results indicate that hard skills have a positive and significant direct effect on both self-awareness and employee performance. Compliance also positively and significantly affects both self-awareness and employee performance. Self-awareness has a positive and significant effect on employee performance. However, soft skills show a positive but non-significant effect on both self-awareness and employee performance. In terms of mediation, self-awareness significantly mediates the effect of hard skills and compliance on employee performance, but does not significantly mediate the effect of soft skills on employee performance.